Robotic and open distal pancreatectomy with celiac axis resection for locally advanced pancreatic body tumors: a single institutional assessment of perioperative outcomes and survival. Issue 10 (October 2016) - Ocuin, Lee M.; Miller-Ocuin, Jennifer L.; Novak, Stephanie M.; Bartlett, David L.; Marsh, J. Wallis; Tsung, Allan; Lee, Kenneth K.; Hogg, Melissa E.; Zeh, Herbert J.; Zureikat, Amer H.
Abstract: Background: Distal pancreatectomy with celiac axis resection (DP-CAR) is an option for T4 tumors of the pancreatic body. We examined the perioperative and oncologic outcomes of open and robotic DP-CAR at a high-volume pancreatic center. Methods: Retrospective review of all consecutive DP-CARs. Patient demographics, 90-day perioperative outcomes, and disease specific survival were collected. Results: 30 DP-CARs were performed (11 Robotic, 19 Open). Both groups had similar preoperative/tumor characteristics, and 27 of 28 PDA patients received neoadjuvant chemotherapy. Robotic DP-CAR was associated with decreased OT (316 vs. 476 min), reduced EBL (393 vs. 1736 ml) and lower rates of blood transfusion (0% vs. 54%) (all p < 0.05). No robotic DP-CAR required conversion. Both groups had similar rates of 90-day mortality, major morbidity, LOS, readmission, and receipt of adjuvant therapy. Similarly, both approaches were associated with high R0 resection rates (82% vs. 79%). At a median follow-up of 33 months, median overall survival for the PDA cohort was 35 months, with no difference in the robotic and open approach (33 and 40 months, p = 0.310). Conclusions: With a median survival approaching 3 years, DP-CAR represents an effective treatment for select patients with locally advanced pancreatic body cancer, regardless of approach.